2016
DOI: 10.1038/onc.2015.499
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced MAPK signaling drives ETS1-mediated induction of miR-29b leading to downregulation of TET1 and changes in epigenetic modifications in a subset of lung SCC

Abstract: Non-small-cell lung cancer is the leading cause of cancer death worldwide and is comprised of several histological subtypes, the two most common being adenocarcinoma (AC) and squamous cell carcinoma (SCC). Targeted therapies have successfully improved response rates in patients with AC tumors. However, the majority of SCC tumors lack specific targetable mutations, making development of new treatment paradigms for this disease challenging. In the present study, we used iterative non-negative matrix factorizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…Possible alterations in expression of the TET genes in lung cancer were first suggested by the observation of reduced levels of their enzymatic product 5hmC in tumor versus normal lung tissue (24). That finding was supported by three studies that showed negative correlation between TET1 expression and miR-767, MAPK/miR29b, and EGFR/CEBPa levels across lung tumors of different histology (29)(30)(31)(32). However, none of those studies analyzed TET1 levels in primary lung tumors compared with normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Possible alterations in expression of the TET genes in lung cancer were first suggested by the observation of reduced levels of their enzymatic product 5hmC in tumor versus normal lung tissue (24). That finding was supported by three studies that showed negative correlation between TET1 expression and miR-767, MAPK/miR29b, and EGFR/CEBPa levels across lung tumors of different histology (29)(30)(31)(32). However, none of those studies analyzed TET1 levels in primary lung tumors compared with normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in other studies in breast cancer and myelodysplastic syndrome (MDS), it was suggested that miRNA-mediated TET2 repression contributes to tumorigenesis [ 96 , 97 ]. It was also reported that miR-22 and miR-29 function as onco-miRs by regulating epigenetic status in cancer [ 98 , 99 ]. In addition to these two miRNAs, several androgen-regulated miRNAs such as miR-125b and miR-200a repressed TET2 -3′UTR, suggesting TET2 is a common target of these AR-induced miRNAs [ 91 ].…”
Section: Targeting Epigenetic Condition By Androgen-regulated Mirnmentioning
confidence: 99%
“…MiR-29b-3p is computationally predicted by miRanda to target the following tumour suppressor genes (TSGs): ADAMTS9, ARRDC3, CASP7, FEM1B, HBP1, HPGD, ING3, NAV3, PTEN, RhoBTBl, SEL1L, SLC5A8, SUV420H2, TET1, TET2 and UVRAG (24). Direct interactions between miR-29b-3p and the 3’-UTRs of colorectal cancer-suppressing TET1 and TET2 have been demonstrated by luciferase assays already (28), (29), (30). Interestingly, a different ITC, phenethyl isothiocyanate, was reported to inhibit the upregulation of miR-29b-3p in mouse lung tissue mediated by environmental cigarette smoke (31).…”
Section: Discussionmentioning
confidence: 97%